Contact allergy to acrylate‐containing nail cosmetics: A retrospective 8‐year study - Steunebrink, Iemke M.; Groot, Anton; Rustemeyer, Thomas (Contact dermatitis, 2024)
Background Over the last 10 years, allergic contact dermatitis (ACD) from acrylate‐containing nail cosmetics (acrylic nails, gel nails, gel nail polish) has been reported repeatedly. Objectives To investigate the frequency and clinical features of ACD in nail cosmetics in a university hospital in Amsterdam, The Netherlands. Patients and Methods A retrospective study in patients diagnosed with ACD from acrylate‐containing nail cosmetics at the Amsterdam University Medical Centers between January 2015 and August 2023. Results Sixty‐seven patients, all women, were diagnosed with ACD from nail cosmetics, representing 1.6% of all individuals and 2.3% of all women patch tested in this period. Sixty‐five of sixty‐seven (97%) subjects had a positive patch test to 2‐hydroxyethyl methacrylate (HEMA). Forty‐nine patients (73%) were consumers and 18 (27%) were professional nail stylists. The sites most frequently affected with dermatitis were the fingers (79%), hands (40%) and the head and/or neck. Avoidance of contact with acrylate‐containing products resulted in complete clearing of dermatitis in 80% of patients. Conclusions ACD from acrylate‐containing nail cosmetics is frequent in women patch tested in Amsterdam. Nearly all were identified by a positive patch test to 2‐hydroxyethyl methacrylate in the (meth)acrylate series or the European baseline series. At the Amsterdam UMC, between 2015 and 2023, 67 women were diagnosed with ACD from nail cosmetics, representing 2.3% of all women patch tested. Forty‐nine patients (73%) were consumers and 18 (27%) were professional nail stylists. Sixty‐five of sixty‐seven (97%) subjects had a positive patch test to 2‐hydroxyethyl methacrylate (HEMA).